Educación mediada por la tecnología y pandemia. ¿Qué se transformó en el proceso de enseñanza-aprendizaje en la escuela colombiana? La visión del docente (Memorias Sifored - Encuentros Educación UAN, 2023)
The COVID-19 pandemic generated a series of unprecedented challenges in all sectors, including the educational field. The abrupt transition to distance education and the limitations imposed by social distancing measures had a profound impact on educational dynamics. These problems cover academic, social, emotional, and technological aspects that affected students, teachers, parents, and the educational community in general. This research has a qualitative approach of an interpretive, descriptive, and analytical type. The objective was to analyze the transformations that technology-mediated education in times of pandemic has generated in the teaching-learning processes in Colombian educational institutions. The main findings cover aspects such as seeing the teaching process as a general and not a particular model based on the rhythms, learning styles, and multiple intelligences of the students; the evaluation phase is seen as an assignment of evaluative grades, not as a permanent and inherent aspect of the teaching-learning process that must be holistic, participatory, flexible, formative, interpretive, and technical; the absence of digital literacy and lack of resources meant that educators had to face in a complex way a change from the face-to-face education model to one mediated by technology. It is necessary to transform the educational system into one of easy access for the entire community, equality in resources, digital literacy for all educational actors, the generation of flexible policies, and the creation of pedagogical practices in accordance with students' needs.
Keywords: pandemic; confinement; technology-mediated education; teaching and learning